2010
DOI: 10.1007/s10140-010-0891-x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of traumatic intracerebral hemorrhage captured with CT imaging: report of a case and the role of serial CT scans

Abstract: Delayed enlargement of a traumatic cerebral contusion can occur subsequent to an initial CT scan, and this can lead to neurological deterioration, brain herniation, and death. Herein, we describe the case of a 76-year-old male who experienced an intracerebral hemorrhage subsequent to a fall and whose injury worsened over time. We summarize the current recommendations in the literature for when to initiate follow-up imaging in patients with traumatic head injury, the risk factors for progression, and the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The phenomenon of ultra early CT missing a significant surgical lesion in the head-injured patient has provoked the debate as to whether serial repeat CT should be adopted and if such a practice is cost effective. [3122526] In this environment, delayed CT is unfortunately the rule rather than an exception and the ultra early CT is rarely done. Follow-up CT is very useful whenever it is indicated, especially in monitoring postoperative patients or those who have not achieved the expected clinical improvement on non-operative management.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of ultra early CT missing a significant surgical lesion in the head-injured patient has provoked the debate as to whether serial repeat CT should be adopted and if such a practice is cost effective. [3122526] In this environment, delayed CT is unfortunately the rule rather than an exception and the ultra early CT is rarely done. Follow-up CT is very useful whenever it is indicated, especially in monitoring postoperative patients or those who have not achieved the expected clinical improvement on non-operative management.…”
Section: Discussionmentioning
confidence: 99%
“…CT scans are a useful tool which can show a stepwise deterioration of TBI which can be tracked to help in not only diagnosing the extent of injuries but also a patient's prognosis. 5 Due to the serious consequences of alcohol and its potential for fatal head related injuries, it is important to increase the awareness of this subject among the greater population.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with TBI, repeated CT scanning has found that intracranial bleeds can develop or expand in the 24 hours after injury and that larger bleeds have a worse prognosis. Delayed enlargement of traumatic intraparenchymal contusions and hematomas is the most common cause of clinical deterioration and death in patients who had a lucid interval after TBI (4) .…”
Section: Introductionmentioning
confidence: 99%